2016
DOI: 10.1007/s12035-016-9685-9
|View full text |Cite
|
Sign up to set email alerts
|

Perforin Promotes Amyloid Beta Internalisation in Neurons

Abstract: Studies on the mechanisms of neuronal amyloid-β (Aβ) internalisation are crucial for understanding the neuropathological progression of Alzheimer's disease (AD). We here investigated how extracellular Aβ peptides are internalised and focused on three different pathways: (i) via endocytic mechanisms, (ii) via the receptor for advanced glycation end products (RAGE) and (iii) via the pore-forming protein perforin. Both Aβ and Aβ were internalised in retinoic acid differentiated neuroblastoma (RA-SH-SY5Y) cells. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
1
18
1
Order By: Relevance
“…It also binds to many other proteins (albeit with lower affinities) found elsewhere in the blood and brain. Under conditions of BBB leak, the influx of vascular A␤ 42 into the brain leads to the formation of A␤ 42 -␣7nAChR complexes on neuronal cell surfaces, which are subsequently internalized, presumably via endocytosis, and accumulate readily within the lysosomal compartment of these cells [35,36]. Mechanisms driving internalization of A␤ 42 and intraneuronal accumulation remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…It also binds to many other proteins (albeit with lower affinities) found elsewhere in the blood and brain. Under conditions of BBB leak, the influx of vascular A␤ 42 into the brain leads to the formation of A␤ 42 -␣7nAChR complexes on neuronal cell surfaces, which are subsequently internalized, presumably via endocytosis, and accumulate readily within the lysosomal compartment of these cells [35,36]. Mechanisms driving internalization of A␤ 42 and intraneuronal accumulation remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Lana et al . demonstrated that Aβ‐42 colocalizes with ER, lysosome, and mitochondria of differentiated SH‐SY5Y cells. Since in the depolymerized state of microtubules, Aβ‐42 resided only at the surface of membrane, thus depolymerization of microtubules possibly disturbs the endocytic transport of the peptides.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, microtubules carry Ab peptides from the vicinity of plasma membrane to its destination which can be ER, mitochondria, Golgi bodies, or other cell organelle. Lana et al [4] demonstrated that Ab-42 colocalizes with ER, lysosome, and mitochondria of differentiated SH-SY5Y cells. Since in the depolymerized state of microtubules, Ab-42 resided only at the surface of membrane, thus depolymerization of microtubules possibly disturbs the endocytic transport of the peptides.…”
Section: Role Of Microtubules In the Transfer Of Ab-42mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike STZ, exogenous (similar to endogenous) Aβ peptide fragments seem to lack selectivity towards membrane molecular targets since the intracellular intake of Aβ peptides is not operated via a selective transporter. Instead, three different pathways of its internalization have been proposed; for both Aβ 1-40 and Aβ 1-42 endocytic mechanisms seem to be the major ones although both could enter a neuron via the pore-forming protein perforin, while only Aβ 1-42 was shown to enter via the receptor for advanced glycation end products (RAGE) (Lana et al 2017). Endocytosis is two times more efficient for soluble Aβ 1-42 than for soluble Aβ 1-40 but both are predominantly taken up via clathrin-and dynaminindependent mechanisms (Wesen et al 2017).…”
Section: Molecular Targets Of Selective Toxicitymentioning
confidence: 99%